The correlation between stroke characteristics and stroke effect of young table tennis players - Xiao, Y.; Xiao, Y.; Lu, M.; Zeng, Y. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: An optimal stroke is essential for winning table tennis competition. The main purpose of this study was to examine the correlations between the stroke characteristics and the stroke effect. METHODS: Forty-two young table tennis players were randomly selected from China Table Tennis College (Mage=14.21; Mheight=1.57m; Mweight=46.05 kg, right-hand racket, shake-hands grip, no injuries in each joint of the body). The high-speed infrared motion capture system was used to collect the data of stroke characteristics, and the high-speed camera was used to measure the spin speed of the stroke. The influence of stroke characteristics on stroke effect was analyzed. RESULTS: The time duration of backswing and forward motion were significantly correlated with ball speed (r=-0.403, P<0.01; r=-0.390, P<0.01, respectively) and spin speed (r=-0.244, P=0.027; r=-0.369, P<0.01, respectively). The ball speed was positively correlated with the linear velocity of right wrist joint (r=0.298, P<0.01), and the angular velocity of right elbow joint (r=0.219, P=0.013), right hip joint (r=0.427, P<0.01) and right ankle joint (r=0.443, P<0.01). The spin speed was positively correlated with the linear velocity of right wrist joint (r=0.238, P=0.031), and the angular velocity of right elbow joint (r=0.172, P=0.048) and right hip joint (r=0.277, P=0.012). The placement had a negative correlation with the angular velocity of right knee joint (r=-0.246, P=0.026). CONCLUSIONS: The time allocation of the three phases of backspin forehand stroke had an important correlation with stroke effect, especially the ball speed and spin speed. The movement of the right wrist joint and right ankle joint were mainly correlated with the ball speed of the stroke. The spin speed of the stroke was mainly correlated with the movement of the right wrist joint. The placement of the stroke was mainly correlated with the rotation of the right knee joint.